Cost-effectiveness analysis of EGFR mutation testing and gefitinib as first-line therapy for non-small cell lung cancer. Issue 1 (October 2015) - Narita, Yusuke; Matsushima, Yukiko; Shiroiwa, Takeru; Chiba, Koji; Nakanishi, Yoichi; Kurokawa, Tatsuo; Urushihara, Hisashi
Highlights Cost-effectiveness of first-line gefitinib therapy with EGFR testing is examined using Markov model. Combination use of gefitinib and EGFR testing for NSCLC is cost-effective in Japan. Our results are robust with several sensitivity and scenario analyses.